1983
DOI: 10.1016/0092-8674(83)90444-0
|View full text |Cite
|
Sign up to set email alerts
|

RecA-independent recombination between direct repeats of IS50

Abstract: Recombination between the IS50 sequences that flank Tn5 has been found to occur readily after the transformation of E. coli recA strains with a plasmid that contains direct repeats of these sequences. Analysis of mutants of IS50 indicates that the polypeptide encoded by IS50 that is required for transposition is also required for the recombination. Surprisingly, the mechanism of recombination appears to be similar to general homologous recombination rather than site-specific recombination. This IS50 recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…If such cointegrates are intermediates in TnS transposition, then resolution may be partly dependent on host recombination/repair functions (e.g., type RecBC RecF nucleases) that may vary between bacteria. Previous results (26) suggest that IS50 p58 protein can catalyze not only transposition but also resolution of tandem;, directly repeated IS50 sequences that configure transient cointegrate structures in E. coli. However, other studies have concluded that TnS transposes in E. coli by a conservative, post-replicative mechanism because cointegrate structures are not observed (1, 2).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…If such cointegrates are intermediates in TnS transposition, then resolution may be partly dependent on host recombination/repair functions (e.g., type RecBC RecF nucleases) that may vary between bacteria. Previous results (26) suggest that IS50 p58 protein can catalyze not only transposition but also resolution of tandem;, directly repeated IS50 sequences that configure transient cointegrate structures in E. coli. However, other studies have concluded that TnS transposes in E. coli by a conservative, post-replicative mechanism because cointegrate structures are not observed (1, 2).…”
Section: Discussionmentioning
confidence: 95%
“…Because KpnI digestion of mutant genomic cointegrates would be expected to yield recombinant plasmids containing an IS50 triplication, the stability of such recombinant plasmids was suspect on theoretical grounds. At least two copies of IS50 would be in a directly repeated orientation and thus be a template for ISSOR-mediated resolution (26) or homologous recombination, both of which would result in excision and loss due to segregation of the recombinant DNA insert. Therefore, in a second protocol, EcoRI was substituted for KpnI; EcoRI cuts the cat gene DNA sequence of pVP2021 once (Fig.…”
mentioning
confidence: 99%
“…Either the loss of homologous recombination was very recent, or such transfers could have occurred in a RecA-independent manner. For example, plasmids could have been transferred into Lv-StB cells, followed by the RecA-independent transposition of genes to the chromosome (Harmer and Hall, 2016; Zupancic et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the recombination between the direct repeats of IS1 on pMCR16 can be prevented by introducing the AT mutation. The IS-catalyzed recombination resembles the homologous recombination observed between direct repeats of IS50 (38)…”
Section: Transcription From Pl During Transformation Of Pmcr16mentioning
confidence: 92%